Implementasi Fungsi-Fungsi Manajemen Dakwah Dalam Kegiatan Keagamaan Di Masjid Al-Ikhlash Desa Marindal 1 - Dini Nadila; Ilham Mirzaya Putra (Jurnal Dakwah Tabligh, 2025)
This study aims to analyze the implementation of da’wah management functions in religious activities at the Al-Ikhlash Mosque, Marindal 1 Village. The mosque as the center of community development requires good management so that da’wah activities run optimally. This study uses a descriptive qualitative approach with field study methods through interviews, observation, and documentation. The results showed that the functions of da’wah management-planning, organizing, implementing, and evaluating-have been systematically applied by the mosque management. The application of these functions plays an important role in increasing the effectiveness of religious programs, strengthening congregational participation, and making the mosque a center of community empowerment. However, there are also challenges such as limited resources and uneven congregational involvement. Therefore, inclusive and flexible management is needed so that da’wah remains relevant and sustainable. The results of the study prove that careful planning, good coordination, and regular evaluation can increase the effectiveness of religious activities in this mosque. This study makes it clear that good da’wah management through the application of appropriate management functions will increase the effectiveness of religious activities, so that they can benefit the wider community.